Strategi Pemilihan Media Pembelajaran Berbasis ACTION: Studi Komparatif Efisiensi Zoom Meeting, Google Meet, dan Microsoft Teams di UIN Syarif Hidayatullah Jakarta - Aolia Lavianis; Nayla Adibah; Rizka Ramdhina Anwar; Nada Adha; Muhammad Zaki Maulida Fauzan; Hesti Kusumaningrum (Lembaga Pengembangan Kinerja Dosen, 2026)
Digital transformation in higher education has created a new paradigm in instructional interACTION, especially in the use of synchronous learning platforms. This study evaluates the strategy of choosing learning media between Zoom Meeting, Google Meet dan Microsoft Teams using the ACTION framework (Access, Cost, Technology, Interactivity, Organization, Novelty). This study is set against the background of academic adjustment policies at UIN Syarif Hidayatullah Jakarta, where lectures were moved to a full online format during the Ramadan period to support learning effectiveness and the solemnity of worship. The main focus of the research is to analyze the level of media inclusivity based on the burden of quota costs (cost) and the technological readiness of devices (technology) owned by students. The method used is a comparative study with a descriptive survey approach to active students. The results of the study are expected to provide recommendations for educators in choosing the most efficient and supportive platform for the economic and technical conditions of students in the digital transition period.